Male infertility and environmental factors. Issue 2 (2019) - Perheentupa, Antti
Abstract : Semen quality in men is decreasing. Numerous chemicals act as endocrine-disrupting agents and their detrimental effect on fertility and spermatogenesis has been shown in rodent studies. Consequences in humans are challenging to study and effects of fetal exposure on fertility are apparent only 2 decades later. Appropriate animal models are needed to study the reproductive effects of the thousands of chemicals that humans come in contact with. The burden of proof of chemical safety must shift from the individual and health care provider to the manufacturers similar to the licensing of medical drugs.